English Language Teaching Strategies in Developmentally Appropriate Practice - Aca, Natasya Putri; Nopita, Dewi; Satria, Benni (Universitas Maritim Raja Ali Haji (UMRAH), 2024)
This research aimed to know what are English Language Teaching Strategies in Developmentally Appropriate Practice. developmentally appropriate practice was a learning activity that recognized that each student had different needs and abilities. In developmentally appropriate practice, students were provided with various choices in terms of learning materials, teaching methods, and assessment. The qualitative research was a research design for this research. The study was conducted in SMPN 1. The subject of the research was an English teacher of SMPN 1 Tanjungpinang. The researcher used a purposive sampling technique to select the subject. The researcher only chose an English teacher for the subject of the study because in the school, there was only one teacher implementing developmentally appropriate practice. The research used observation, interview, and documentation as instruments to collect data. English Language Teaching Strategies in Developmentally Appropriate Learning used by teachers were Video-assisted learning (VAL), Picture Stories, Context Clues, and Group-Work strategies.